Beijing 2022 Olympic and Paralympic Winter Games Sustainability Plan (Beijing Organising Committee for the 2022 Olympic and Paralympic Winter Games, 2020)
Beijing Organising Committee for the 2022 Olympic and Paralympic Winter Games (Beijing 2022) published the Beijing 2022 Olympic and Paralympic Winter Games Sustainability Plan (hereinafter referred to as Sustainability Plan) on 15 May. This plan was developed jointly by the People`s Government of Beijing Municipality, the People`s Government of Hebei Province, and the Beijing 2022. The plan serves as a programmatic document guiding the sustainability work of the Beijing 2022 Games and is being implemented throughout the entire process of the Games. The sustainability plan reflects the Beijing 2022 mission of being "green, inclusive, open and clean", and the reforms introduced through Olympic Agenda 2020 - the strategic roadmap for the future of the Olympic Movement. It is also aligned with the United Nations 2030 Agenda for Sustainable Development. The plan promotes the Beijing 2022 Games` sustainability vision of "Sustainability for the Future" and the overall objective of "creating a new example for staging events and regional sustainability", featuring three key themes of "Positive Environmental Impact", "New Development for the Region", and "Better Life for the People". These three themes are supported by 12 actions, under which there are 37 key tasks and 119 specific measures that cover the environment of the competition zones, regional development, and improvement of well-being for host communities in Beijing and Zhangjiakou.